Biochemical evaluation of phenylketonuria (PKU): from diagnosis to treatment - Leticia Belmont-Martínez; Cynthia Fernández-Lainez; Isabel Ibarra-González (Instituto Nacional de Pediatría, 2014)
Non treated phenylketonuria (PKU) has serious consequences such as growth retardation and intellectual impairment along with symptoms like erythematous eczema, fair skin and hair, seizures, autistic conduct and aggressive behavior. Pre-symptomatic biochemical diagnosis consists of identifying patients by blood phenylalanine (Phe) quantification through newborn screening. The confirmation is based on determining serum Phe and tyrosine levels. There is a wide spectrum of hyperphenylalaninemia clinical presentation, which ranges from mild forms which do not require nutritional treatment to the most severe form of the disease known as classic PKU. The aim of treatment is to avoid irreversible neurological impairment by stabilizing blood Phe level and keeping it within therapeutic concentration range. Once PKU diagnosis has been established, there are several criteria to decide when it is necessary to initiate treatment, we start it if Phe level is > 360 micromol/L (6 mg/L). Besides periodical Phe and Tyr testing, biochemical follow-up includes the measurement of necessary elements that guarantee normal physical and intellectual development such as selenium, zinc, B12 vitamin, folates, iron and long chain fatty acids. Clinical context is as important as biochemical status so periodic evaluation of nutritional, medical, social and psychological aspects should be included.